1990
DOI: 10.1002/pts.2770030206
|View full text |Cite
|
Sign up to set email alerts
|

Cause of catty odour formation in packaged food

Abstract: In t w o different 'cook-in-the-bag' ham products packed i n polyamide-ethylene ionomer laminate pouches, the same obtrusive catty off-odour was complained about. In this paper the analytical resolution of a complex off-odour problem is described.Identification of the catty odour as the mesityl oxide-hydrogen sulphide adduct 4-methyl-4-mercaptopentan-2-one is followed by investigating the formation o f the o f fodour w i t h the aid of different model experiments. It is pointed out that the ethylene ionomer ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…The compound is an interaction product of 2-methyl-2,4-pentanediol, used as a solvent coating for ink adherence, and formaldehyde (from an unknown source). In another example, the observed "catty" off-odour in cook-in-the-bag ham products was ascribed to the mesityloxidehydrogen sulphide adduct 4-methyl-4-mercaptopentan-2-one resulting from a complex sequence of interactions between a residual red printing solvent, components of the packaging materials (diacetone alcohol in polyamide-ethylene ionomer laminate, identified by HS-GC, GC-sniffing, GC-FID and GD-MS) and food ingredients [88,89]. Piringer et al [8] have reported the identification of off-odours in packaging materials (collection, concentration, separation by GC and identification by MS).…”
Section: Instrumental Methods In Off-odour/ Off-taste Problemsmentioning
confidence: 99%
“…The compound is an interaction product of 2-methyl-2,4-pentanediol, used as a solvent coating for ink adherence, and formaldehyde (from an unknown source). In another example, the observed "catty" off-odour in cook-in-the-bag ham products was ascribed to the mesityloxidehydrogen sulphide adduct 4-methyl-4-mercaptopentan-2-one resulting from a complex sequence of interactions between a residual red printing solvent, components of the packaging materials (diacetone alcohol in polyamide-ethylene ionomer laminate, identified by HS-GC, GC-sniffing, GC-FID and GD-MS) and food ingredients [88,89]. Piringer et al [8] have reported the identification of off-odours in packaging materials (collection, concentration, separation by GC and identification by MS).…”
Section: Instrumental Methods In Off-odour/ Off-taste Problemsmentioning
confidence: 99%
“…The odour threshold of this hydrogen sulphide/mesityl oxide adduct in bland foods is of the order of 0.0 I ppb. Franz et al (1990) described an extensive investigation to trace the source of a catty odour in a cook-in-the-bag ham product and showed by analysis and synthesis experiments that the odour was the previously mentioned hydrogen sulphide/mesityl oxide adduct. The investigations demonstrated that the mesityl oxide originated from diacetone alcohol, which was present as a residual solvent in red printing.…”
Section: Some Reported Odour and Taint Investigationsmentioning
confidence: 99%
“…Whereas sensory techniques provide information about overall odour perception, olfactory thresholds and consumer acceptability, instrumental analyses identify and quantify the single volatile compounds that compose an odorous mixture. The most common technique used to evaluate the odour of packaging materials is gas chromatography coupled with mass spectrometry (Franz et al 1990;Marin et al 1992;Linssen et al 1993;Linssen and Roozen 1994;Sanders et al 2005, Willoughby et al 2003Villberg and Veijanen 1998;Bravo et al 1992;Hodgson et al 1998;Pugh and Guthrie 2000;Ziegleder 1998) (Ezquerro et al 2002(Ezquerro et al , 2003a(Ezquerro et al , 2003b(Ezquerro et al , 2003c(Ezquerro et al , 2003dKusch and Knupp 2004;).…”
Section: Introductionmentioning
confidence: 99%